PERAN MEDIA DALAM KOMUNIKASI POLITIK JELANG PEMILIHAN UMUM KEPALA DAERAH TAHUN 2017 DI KABUPATEN ACEH BARAT - Aminah Aminah (SOURCE : Jurnal Ilmu Komunikasi, 2016)
Media in Political Communication ahead of the election widely used by the partner Regent and deputy Regent candidates to influence and seek sympathizers from the community, as happened in Aceh Barat District. Of the three candidates, namely pair H. T. Alaidin Syah and H. Kamaruddin, the couple H. Ramli MS and H. Banta Puteh Syam and the couple Fuad Hadi, SH., MH and drh. Muhammad Arif. This study describes the role of the media are executed by each pair of candidates Regent and deputy Regent of Aceh Barat ahead of the election simultaneously throughout Indonesia. This paper is based on a review of literature as well as by looking at the phenomenon of campaign located along Aceh Barat district. Based on the writer's observation, that each pair has the creativity respectively in the campaign (conveying political messages). Couple H. T. Alaidin Syah and H. Kamaruddin choose a political message by using the phrase "KAMO HANA JANJI ALHAMDULILLAH LE BUKTI YANG NYATA" and "Lanjutkan!". While the pair H. Ramli MS and H. Banta Puteh Syam chose the phrase "KATROEH WATEE Tabalah JASA RAKYAT. Different from other couples Fuad Hadi, SH., MH and drh. Muhammad Arif also choose the appropriate sentence to attract public attention Aceh Barat district by using the phrase "BONGKAR KEBIASAAN LAMA, YANG “TUA” SUDAH PERNAH SAATNYA YANG “MUDA” MEMBENAH. And "SOLUSI NYATA UNTUK ACEH BARAT ". Each pair of candidates make the process of media planning and advertising strategies by paying attention to advertising, advertising budgets, strategies and the role of media messages which take into account the selection of the target audience, purpose specification, selection of media and facilities and purchase of media. Keywords: Role of Media, Political Communication and Election